A Novel Wineglass Shaped Wide Band Antenna for TV White Space Communication - Ahmad Raza, Ghulam; Saini, Garima; Kumar, Naveen (International Journal of Engineering and Technology, 2018)
This paper presents a novel patch antenna for TV white spaces applications. The shape of the proposed antenna is based on the shape of a wineglass. The dimension of the proposed antenna is 170 mm x 120 mm x 1.6 mm. After simulation, the proposed antenna resonates at 703 MHz with a return loss of -21.97 dB and covering a bandwidth from 495 MHz to 1540 MHz. Overall bandwidth coverage is 1045 MHz. So the proposed antenna is a wide band antenna covering almost the entire TV Ultra High Frequency (UHF) range. Simulated VSWR obtained at 703 MHz is 1.38 dB and simulated gain is 2.32 dB. The proposed antenna is fabricated using FR4 substrate and tested on Vector Network Analyzer (VNA). The measured return loss of fabricated antenna is -20.20 dB at 596 MHz. Proposed antenna shows the simulated radiation efficiency of 95%. Simulated and measured results showed good match between them. Proposed design is compared with few designs available in literature to validate its novelty and advantages.Â